2021
DOI: 10.3390/educsci11020060
|View full text |Cite
|
Sign up to set email alerts
|

#Mathathome during the COVID-19 Pandemic: Exploring and Reimagining Resources and Social Supports for Parents

Abstract: During the COVID-19 pandemic, schools abruptly transitioned to emergency remote instruction. Consequently, expectations for parental involvement in school mathematics rose to unprecedented levels. We sought to understand the experiences of parents to reimagine possibilities for engagement in mathematics during and beyond the pandemic. Leveraging data from tweets using #mathathome and survey responses from parents, we identified who supported continued mathematics learning at home and explored the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
1
11
1
4
Order By: Relevance
“…Despite these positive experiences, worldwide there is the common feeling that the e-learning needs to be improved ( Fauzi and Sastra Khusuma, 2020 ; Putri et al, 2020 ; Rasmitadila et al, 2020 ), technology implemented ( Dube, 2020 ; Fauzi and Sastra Khusuma, 2020 ; Rasmitadila et al, 2020 ), teachers more trained ( Dias et al, 2020 ; Putri et al, 2020 ; Szente, 2020 ), and integrated grade-specific approaches are needed ( Zhao et al, 2020 ). In general, teachers found a lower learning quality with respect to traditional lessons ( Lucisano, 2020 ), and families had negative beliefs about the values and benefits of online learning, retaining that the family-school partnerships has not yielded compelling results and preferring traditional methods ( Dong et al, 2020 ; Firmanto et al, 2020 ; Harper et al, 2021 ; Lee et al, 2021 ; Thorell et al, 2021 ). These findings differ from the Aeris reality, but we must point out that the initiatives described in this manuscript are specifically thought for 0–3 aged children, therefore dealing with simple activities that use materials easily available at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these positive experiences, worldwide there is the common feeling that the e-learning needs to be improved ( Fauzi and Sastra Khusuma, 2020 ; Putri et al, 2020 ; Rasmitadila et al, 2020 ), technology implemented ( Dube, 2020 ; Fauzi and Sastra Khusuma, 2020 ; Rasmitadila et al, 2020 ), teachers more trained ( Dias et al, 2020 ; Putri et al, 2020 ; Szente, 2020 ), and integrated grade-specific approaches are needed ( Zhao et al, 2020 ). In general, teachers found a lower learning quality with respect to traditional lessons ( Lucisano, 2020 ), and families had negative beliefs about the values and benefits of online learning, retaining that the family-school partnerships has not yielded compelling results and preferring traditional methods ( Dong et al, 2020 ; Firmanto et al, 2020 ; Harper et al, 2021 ; Lee et al, 2021 ; Thorell et al, 2021 ). These findings differ from the Aeris reality, but we must point out that the initiatives described in this manuscript are specifically thought for 0–3 aged children, therefore dealing with simple activities that use materials easily available at home.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, childhood services and schools had to bridge the gap between need for children to learn and socialize and their isolation due to the pandemic, through actions aimed at actively engaging families in promoting child development and wellbeing. For this reason, following the COVID-19 outbreak, schools all over the world reorganized and activated new services to support families and guarantee children educational continuity (see for example, Bubb and Jones, 2020;Caffo et al, 2020;Dong et al, 2020;Dube, 2020;Ferraro et al, 2020;Parmigiani et al, 2020;Putri et al, 2020;Rasmitadila et al, 2020;Zhao et al, 2020;Harper et al, 2021). However, these studies mainly included children and adolescents from 3 years old up to 18 years old, and only few studies included children younger than 3 years and their families (Listyaningrum et al, 2020;Szente, 2020;Lee et al, 2021;Meoded Karabanov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In setting up ERT, schools and teachers developed different strategies and reported a variety of experiences. Focusing on the U.S., Harper et al, ( 2021 ) found that school responses to emergency remote instruction used mostly asynchronous delivery modes, which puts high demands on parental engagement. In contrast, specifically for the case of mathematics education, Drijvers et al, ( 2021 ) found that teachers in Flanders and The Netherlands, and to a lesser extent in Germany, moved to synchronous delivery modes such as videoconferencing to deliver their teaching, and seemed to be gaining confidence with that mode.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…En el caso de Europa, se abordan las percepciones de los tutores para reforzar el vínculo escuela-familia y para identificar áreas de mejora en las redes de apoyo generadas en las familias (Cano-Hila & Argemí-Baldich, 2021;Vicente et al, 2020). Particularmente, un estudio abarca a participantes de diferentes países, diagnosticando las estrategias de apoyo que brindan los tutores a sus hijos para el aprendizaje de las matemáticas durante el confinamiento (Harper et al, 2021).…”
Section: Madres-padres De Familia Y Educación a Distanciaunclassified
“…Llerena y Sánchez (2020) agregan que, debido a la limitada comunicación entre padres de familia y docentes, se desencadenan dificultades para la retroalimentación del proceso pedagógico. Harper et al (2021) destacan que en la educación emergente los padres de familia demandan a los docentes las asesorías individualizadas. 6.…”
Section: Desafíos Coincidentes En Contexto Urbano Y Ruralunclassified